2021
DOI: 10.1016/s2352-4642(21)00030-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the new SARS-CoV-2 variant B.1.1.7 on children and young people

Abstract: Effect of the new SARS-CoV-2 variant B.1.1.7 on children and young people The clinical impact of the new SARS-CoV-2 lineage B.1•1.7 on children and young people (aged 18 years or younger) regarding acute respiratory COVID-19 is yet to be fully defined. Media reports of increases in admissions to hospital and more serious illness in children and young people have resulted in public confusion and implicated the B.1.1.7 variant as a more pathogenic infection within this group. 1,2 This uncertainty has necessitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 3 publications
4
90
0
1
Order By: Relevance
“…Our finding of lower age specific hazard ratio estimates in younger age groups are consistent with a previously reported age specific adjusted odds ratio of hospital admission of 1.0 for patients aged 0-19 with versus without SGTF variants in seven EU/EEA countries but contrasts with a study in Denmark that reported an adjusted odds ratio of 1.84 for patients aged 0-29 with SGTF variants. 23 24 Children and adolescents aged ≤18 who were admitted to hospital with covid-19 in November 2020 to January 2021 at King’s College Hospital in London (where the local prevalence of B.1.1.7 was high) were reported to have had similar clinical severity and treatment requirements to those admitted in March to May 2020, 25 corroborating the suggestion that patients in the youngest age groups experience no more severe disease if infected with B.1.1.7 than with wild-type SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of lower age specific hazard ratio estimates in younger age groups are consistent with a previously reported age specific adjusted odds ratio of hospital admission of 1.0 for patients aged 0-19 with versus without SGTF variants in seven EU/EEA countries but contrasts with a study in Denmark that reported an adjusted odds ratio of 1.84 for patients aged 0-29 with SGTF variants. 23 24 Children and adolescents aged ≤18 who were admitted to hospital with covid-19 in November 2020 to January 2021 at King’s College Hospital in London (where the local prevalence of B.1.1.7 was high) were reported to have had similar clinical severity and treatment requirements to those admitted in March to May 2020, 25 corroborating the suggestion that patients in the youngest age groups experience no more severe disease if infected with B.1.1.7 than with wild-type SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Since March 2020, most governments around the world have closed schools and other educational institutions in an attempt to contain the diffusion of the COVID-19 pandemic, with an estimated dramatic impact on the education of over 850 million children and youths [1][2][3][4]. On the other hand, epidemiological data show that people aged 1-18 years tend to develop asymptomatic/paucisymptomatic disease, and, overall, present a significantly more favorable outcome than adults [5][6][7]. Furthermore, younger children seem to be less susceptible to infection and transmitting the disease compared to older children, adolescents, and adults [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, younger children seem to be less susceptible to infection and transmitting the disease compared to older children, adolescents, and adults [3,5]. However, with the emergence of new variants, the risk of disease transmission and outcomes in children deserve close surveillance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Another UK based study of a cohort of 198,420 patients reported an increase in disease severity, critical care admission and 60% increased risk of mortality associated with B.1.1.7 [ 33 ]. An increase in the pediatric cases with COVID-19 in the UK during the second wave of the pandemic is attributed to B.1.1.7 prevalence and high transmission nonetheless, no significant increase in morbidity or mortality on these young individuals were observed [ 34 ]. Pertaining to vaccine efficacy, despite being 45% more transmissible, prioritized vaccination with an mRNA vaccine coupled with proactive surveillance programs was shown to prevent B.1.1.7 infections especially in the elderly [ 35 ].…”
Section: B117: ‘Uk Variant’mentioning
confidence: 99%